PELATIHAN INTERVAL MODEL LARI GAWANG 45 CM LEBIH MENINGKATKAN LOMPATAN LOMPAT JAUH GAYA JONGKOK DARIPADA PELATIHAN INTERVAL MODEL LARI GAWANG 30 CM PADA SISWA SMP NEGERI 5 KUPANG TIMUR SATAP KABUPATEN KUPANG - O. Lenati, Cornalius; Pangkahila, J. Alex.; Fufu, Oktovianus (Sport and Fitness Journal; Volume 2, No.2, 2014, 2014)
The long jumpsquat style is a partof the jumpnumberwhichaimstomovethebodyfarforwardwithoutfallingover backwardswhilelanding. The research of SMPNegeri 5 studentsEast KupanSatapKupang Regency has beendonetoimprove thejumping movementlong jumpsquat style. Inthis studyconductedwithtwotypesoftraining that the intervaltraining hurdle run model30cm(3 reps5sets), andintervaltraininghurdle runmodel45cm(5 reps3sets). The trainingis doneinthe yard of SMPNegeri 5 East Kupang SatapKupang Regency beginning at4 pm - 6pmforeightweekswith a frequency ofthreetimes a week. The samples wereselected simplerandomlyas many as24 peoplewhohave met theinclusion and exclusion criteria. Theselectedsamplewas dividedintotwogroups, so thateach grouptotaled12 people, andeachgroupwas giventhe sametraining, but differentinrepsandsets. Group-1 isgiveninterval traininghurdle run model30cm(3 sets of5reps) andgroup2 is given hurdlerun model45cm(5 reps3sets). The data is a jump result was takenafterthetrainingfinished, is analyzedwithcomputer software. T-paired test wasusedtoanalyzethe differences of the jumping movement long jumpsquat stylebetweenbefore andaftertrainingineach groupand the t-unpairedtestusedto analyze thedifferences of thejumping movement long jumpsquat stylebetween each groupseitherat theinitialtestandfinal test. Limit ofsignificanceused wasp<0.005. The mean of jumpingmovement long jumpsquat styleonthe interval traininghurdlerunmodel30cmbeforetrainingand after training2.21metersto 3.59meterswhichshowedastatisticallysignificant differencep=0.02(p <0.05). Themeanjumpbeforetrainingonintervaltraining ofhurdle run model 45cmbeforetraining is2.21metersand after training is4.30meterswhichalsoshowed asignificantdifferencep=0.002p<0.05). It is meansthat theintervaltraining ofhurdle runmodel45cmis more increase the jumping movement long jumpsquat styleof SMP Negeri5studentsEast KupangSatapKupang Regency.
Keywords: intervaltraininghurdle run model, jumping movement long jumpsquat style